AGEN CERDAS PEMBELAJARAN BAHASA SUNDA UNTUK SEKOLAH DASAR KELAS II - Nining Suryani (Universitas Bina Sarana Informatika Kota Sukabumi, 2016)
The learning method is currently done is face to face with the learning process Sundanese language subjectswith time once a week with a period of 1 hour so that the provision of material Sunda language is very limited.By this time limitation makes it difficult students in understanding the material provided. For that we need a funway of learning that should be improved by the teacher to the subject matter can be conveyed properly to thestudents so we need a tool for students to learn anytime and anywhere with a sense of fun. Intelligent agentsSundanese language learning can be one way to study for the selection of students for the intelligent agent is funand not boring in its use. This study uses data collection, analysis, project design, manufacture and testingprojects on intelligent agents that will be designed.